The Guinea Pig as a Model for Sporadic Alzheimer’s Disease (AD): The Impact of Cholesterol Intake on Expression of AD-Related Genes - Sharman, Matthew; Moussavi Nik, Seyyed; Chen, Mengqi; Ong, Daniel; Wijaya, Linda; Laws, Simon; Taddei, Kevin; Newman, Morgan; Lardelli, Michael; Martins, Ralph; Verdile, Giuseppe (Public Library of Science, 2013)
We investigated the guinea pig, Cavia porcellus, as a model for Alzheimer’s disease (AD), both in terms of the conservation of genes involved in AD and the regulatory responses of these to a known AD risk factor - high cholesterol intake. Unlike rats and mice, guinea pigs possess an Ab peptide sequence identical to human Ab. Consistent with the commonality between cardiovascular and AD risk factors in humans, we saw that a high cholesterol diet leads to up-regulation of BACE1(b-secretase) transcription and down-regulation of ADAM10 (a-secretase) transcription which should increase release of Ab from APP. Significantly, guinea pigs possess isoforms of AD-related genes found in humans but not present in mice or rats. For example, we discovered that the truncated PS2V isoform of human PSEN2, that is found at raised levels in AD brains and that increases c-secretase activity and Ab synthesis, is not uniquely human or aberrant as previously believed. We show thatPS2V formation is up-regulated by hypoxia and a high-cholesterol diet while, consistent with observations in humans, Ab concentrations are raised in some brain regions but not others. Also like humans, but unlike mice, the guinea pig gene encoding tau, MAPT, encodes isoforms with both three and four microtubule binding domains, and cholesterol alters the ratio of these isoforms. We conclude that AD-related genes are highly conserved and more similar to human than the rat or mouse. Guinea pigs represent a superior rodent model for analysis of the impact of dietary factors such as cholesterol on the regulation of AD-related genes